Wood Waste Management: Sawdust as a Planting Media during the COVID-19 Pandemic at Sindangmekar Village, Dukupuntang Subdistrict, Cirebon District - arie arie; Lili Amalia; Rosalia Rahayu (Community Development Journal, 2021)
One of the growing industries in Indonesia is the woodworking industry. Wood waste is waste or parts of the wood that no longer has economic value but may still be used at different processes and times. The woodworking industry produces wood waste in 22% wood scraps, 8% wood chips, and 10% sawdust. The fundamental problem in the woodworking industry at Sindangmekar Village was the lack of understanding and practice in wood waste management. Through the socialization of wood waste management as planting media, community service aims to increase knowledge regarding wood waste management. In addition, it can improve practice to manage sawdust as a planting media. Furthermore, it has economic value and becomes one of the solutions to financial problems during the COVID-19 pandemic. The socialization presented materials related to wood waste management and practiced making planting media from sawdust. Thirty participants attended this activity. There was a significant increase in pre-and post-test scores after socialization. In conclusion, socialization regarding wood waste management increases knowledge levels in wood artisans and youth alliance at Sindangmekar Village. In addition, participants can manage wood sawdust as a planting medium. As a result, it can increase the selling value of wood waste, and the surrounding environment becomes clean and healthy.